Proposta de manual para implementação de incubadora de empresas em instituições federais de ensino superior: estudo de Departamento de Oftalmologia e Ciências Visuais - Assumpcao, Wander [UNIFESP] (2020)
The research deals with the study of the implantation of a business incubator in the Department of Ophthalmology of EPM / UNIFESP and presentation of a Work Plan for the incubator. The questions that structured the project development were the feasibility of implementation aiming at practical application and consequent commercialization of products and services in the market (program purpose), as well as the insertion not only of the projects of the students of the Professional Master in Technology, Management and Health. Ocular - Innovation and Perspectives, but also open to the entry of projects and external startups, meeting the requirements of the announcement. These guiding questions determined the general objective of the study and the specific objectives, which were: configuration of the incubator as an articulated space for economic and social development; fostering and encouraging innovation in eye health; application of the Technical and Economic Feasibility Study; technical and behavioral training of eye health entrepreneurs; identification of the profile of graduated companies in terms of the generation of viable jobs for economic and social factors or indicators, as provided for in the National Program for Support to the Implementation of Company Incubators. In order to meet the objectives, the action research was chosen, which enables the researcher to intervene within a social problem and has a base created through a close relationship with an action (incubator implementation), using the work for this purpose. collective and interactive between the participants, requiring a proximity between theory and practice.